2019
DOI: 10.2169/internalmedicine.2882-19
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter Flow Cytometry for the Identification of Neoplastic Plasma Cells in POEMS Syndrome with IgG-kappa Gammopathy: Successful Treatment Using Lenalidomide and Dexamethasone

Abstract: A 72-year-old man presented with a 6-month history of systemic edema. Hyperpigmentation, hemangioma, pleural effusion, IgG-kappa-type monoclonal protein, high vascular endothelial growth factor values, renal failure, and nerve conduction study abnormalities were also present. Multiparameter flow cytometry (MFC) showed 0.2% neoplastic plasma cells (CD38-, CD56-, and kappa-positive; CD19-, CD27-, and lambda-negative) in the bone marrow leading to POEMS syndrome. Cases involving kappa-type POEMS syndrome are extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…CD19 expression in PCs of monoclonal gammopathy of undetermined significance is lower than in normal PCs but higher than in MM PCs, and loss of CD19 has been associated with tumor progression 23 . Several reports referring to the immunophenotype of POEMS syndrome also reported that CD19 was negative 8 , 11 , 24 , 25 , which is consistent with this study, indicating that the monoclonal PCs in POEMS syndrome are immunophenotypically distinct from normal polytypic PCs. On the other hand, one case with CD19 + monoclonal PCs was detected in this study (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…CD19 expression in PCs of monoclonal gammopathy of undetermined significance is lower than in normal PCs but higher than in MM PCs, and loss of CD19 has been associated with tumor progression 23 . Several reports referring to the immunophenotype of POEMS syndrome also reported that CD19 was negative 8 , 11 , 24 , 25 , which is consistent with this study, indicating that the monoclonal PCs in POEMS syndrome are immunophenotypically distinct from normal polytypic PCs. On the other hand, one case with CD19 + monoclonal PCs was detected in this study (Fig.…”
Section: Discussionsupporting
confidence: 91%
“… 1 , 4 These isolated cases have demonstrated either demyelinating polyneuropathy alone or with axonal degeneration, except for 1 case in which the neuropathy was not characterized. 4 , 5 , 6 , 7 However, there was no evidence of demyelinating polyneuropathy in this case. Additionally, all previously reported kappa restricted cases showed evidence of endocrinopathy, which is absent here.…”
Section: Discussionmentioning
confidence: 56%
“…This suggests that the M-protein might be one of the driving factors of the disease. The plasma cell clone producing the M protein is usually λ light chain restricted, but atypically can also present with Kappa light chain restriction [ 10 , 11 ]. Clonal immunoglobulin λ light variable chain (IGLV) was strictly derived from IVLG-1–40 and IVLG-1–44 genes.…”
Section: Pathogenesis Of the Diseasementioning
confidence: 99%